The Spirit of Truth: Johannine Pneumatology in the Letters of Athanasius to Serapion - Issak, Haitham A. (My University, 2018)
Athanasius’ three letters to Serapion were the first comprehensive writings to discuss the divinity of the Holy Spirit. The letter written by Serapion bishop of Thmuis to Athanasius asked him how to deal with a group in the Nile Delta, the Tropici, who denied the deity of the Holy Spirit. Athanasius was in his third exile when he received Serapion’s request. The letters are replete with biblical references in order to support his defense of the divinity of the Holy Spirit. Particularly prominent are the Johannine texts; the Gospel of John and 1 John are cited more than ninety times. This dissertation demonstrates Athanasius’ reliance on John’s writings for the composition of his Letters to Serapion, as well as provides a preliminary exploration of the links between John and Athanasius’ pneumatology.
Keywords: Letters to Serapion; Athanasius; Johannine texts